2010
DOI: 10.1111/j.1749-6632.2010.05917.x
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian genetics of male infertility

Abstract: Infertility is defined as the inability of a couple to conceive despite trying for a year, and it affects approximately 15% of the reproductive-age population. It is considered a genetically lethal factor, as the family lineage stops at that individual with no progeny produced. A genetic defect associated with an infertile individual cannot be transmitted to the offspring, ensuring the maintenance of reproductive fitness of the species. However, with the advent of assisted reproductive techniques (ART), we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 164 publications
(190 reference statements)
0
49
1
1
Order By: Relevance
“…Genetic studies of male sterility identified the causative mutation in 22 of these genes 12 . Deleterious mutations in the testis-exclusive genes are therefore likely to be under strong negative selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic studies of male sterility identified the causative mutation in 22 of these genes 12 . Deleterious mutations in the testis-exclusive genes are therefore likely to be under strong negative selection.…”
Section: Resultsmentioning
confidence: 99%
“…Gene annotation analysis and literature searches show that human testis-exclusive genes are significantly enriched in male reproductive processes ( Table 1), and that mutations in some of these genes cause male infertility and sterility 12 . Thus, deleterious mutations in such genes are likely to be under extreme purifying selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on mouse models as well as human gene mutation have suggested a correlation between genetic causes (e.g. chromosomal aberrations and single gene mutation) and male infertility (Cooke & Saunders 2002, Ferlin et al 2007, Walsh et al 2009, Hwang et al 2010, Shelling 2010. For male infertility with a normal genetic background, stem cell therapy to generate male gametes may represent a promising treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Classic examples of genes, the mutation of which affect male fertility, are the CF transmembrane receptor gene and the androgen receptor gene [15,16]. Mutations in the CFTR gene may lead to congenital bilateral absence of the vas deferens and obstructive azoospermia (observed in approx.…”
mentioning
confidence: 99%